2018
DOI: 10.1177/0145721718759980
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Experiences of Transitioning Their Emerging Adult With Type 1 Diabetes to College

Abstract: Purpose The purpose of this study was to gain a deeper understanding about mothers' experiences of transitioning their emerging adult with type 1 diabetes mellitus to college. Methods A descriptive, qualitative study was conducted with 9 mothers of high school seniors with type 1 diabetes (T1DM) using semi-structured questions via recorded telephone interviews. Results Among the 9 participants, 8 had daughters, and 1 had a son. The thematic analysis resulted in 4 themes: (1) concern for health and safety at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Hybrid closed loop systems have been shown to be especially effective in improving control in the overnight hours 28,29 and may decrease overnight parental burden in the future 30 . The degree to which youth in the study relied on parental intervention and surveillance overnight also speaks to the difficulty experienced by youth as they transition to young adulthood 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid closed loop systems have been shown to be especially effective in improving control in the overnight hours 28,29 and may decrease overnight parental burden in the future 30 . The degree to which youth in the study relied on parental intervention and surveillance overnight also speaks to the difficulty experienced by youth as they transition to young adulthood 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 The degree to which youth in the study relied on parental intervention and surveillance overnight also speaks to the difficulty experienced by youth as they transition to young adulthood. 31 Other studies have examined the distribution of self-management and transition in diabetes management from parent to youth. 29,[32][33][34][35] Continued parental involvement throughout adolescence is associated with better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…In a study describing mothers' experiences of transitioning their youth with type 1 diabetes mellitus, Ness and colleagues revealed mothers' heightened concern during the college transition compared to families of youth without diabetes and concluded that increasing preparedness for diabetes self-management would serve to decrease mothers' stress. 7 In 2018, Lozano and Houtrow outlined models for supporting self-management among young adults, including processes to address modifiable influences at the individual, family, community, and health care system levels. 6 Gaps in self-management support, however, remain.…”
Section: Introductionmentioning
confidence: 99%
“…Parents report difficulty in relinquishing control of diabetes management and express feelings of considerable stress about their adolescent's health and safety. [7][8][9] Increased family conflict, poor self-management, and poor glycemic control often occur during adolescence. 10,11 Family-based educational programs for parents and youth with T1DM promoting parent-adolescent teamwork, family problem solving, communication, and family therapy have demonstrated improvements in family functioning and glycemic control.…”
Section: Introductionmentioning
confidence: 99%